Innovative Organizations Components in Basic Education Institutions in Thailand - Aniruth Boonkua; Ampapan Tuntinakorngul; Pariyaporn Tungkunanan (My University, 2020)
This paper reports the innovative organization's components in basic education institutions in Thailand and the results of confirmatory factor analysis to validate those components.The data for analysis were collected from the samples of 84 school directors, 332 deputy school directors, and 84 heads of ICT department in schools of the Basic Education Commission, Ministry of Education in Thailand for the academic year of 2018, using stratified randomized technique.The tool for data collection was approved questionnaire with high content validity at 0.97.The statistics used to analyse the data included means (M), standard deviation (S.D.), and Confirmatory Factor Analysis (CFA).The results revealed that (1) there were eight components and the highest level of the opinions of its importance was on the components of information and communications technology (ICT) management at 4.67(M) and S.D. at 0.31, and (2) there was a significant resemblance between the theory and the empirical data examined by a confirmatory factor analysis (χ2 = 0.13, χ2 /df= 0.01, GFI=0.99,AGFI= 0.97, RMSEA =0.03).
Keywords: Christian ministry; Strategic Planning and Analysis